2016
DOI: 10.1158/1538-7445.am2016-940
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 940: The role of protein kinase C isoforms in telomerase activity and alphafetoprotein secretion by the hepatocellular carcinoma cell lines

Abstract: Background: Hepatocellular carcinoma (HCC) is the third largest contributor to cancer mortality in the world. Alphafetoprotein (AFP) is synthetized and secreted by the majority of HCCs. Despite its controversial value as classical HCC diagnostic and follow-up marker, the AFP was lately shown to correlate with the volume of liver cancer. It is also useful as a predictive marker for radiotherapy treatment response and patients prognosis. On the molecular level, AFP has a proliferative role in HCC since it acts o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Various studies have shown that PKCε directly phosphorylates AKT at S473 [12] and SMAD3 at S213 [13], activating their respective pathways resulting in uncontrolled cell survival and proliferation. Evidence indicates the role of PKCε in modulating the expression of AFP, which has significance as a diagnostic and followup marker of HCC [14]. PKCε has also shown to facilitate hepatic steatosis and impairment of hepatic insulin signaling, thus, promoting insulin resistance which is a major factor in liver disease and development of HCC in patients with chronic HCV infection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have shown that PKCε directly phosphorylates AKT at S473 [12] and SMAD3 at S213 [13], activating their respective pathways resulting in uncontrolled cell survival and proliferation. Evidence indicates the role of PKCε in modulating the expression of AFP, which has significance as a diagnostic and followup marker of HCC [14]. PKCε has also shown to facilitate hepatic steatosis and impairment of hepatic insulin signaling, thus, promoting insulin resistance which is a major factor in liver disease and development of HCC in patients with chronic HCV infection [15][16][17].…”
Section: Introductionmentioning
confidence: 99%